Epidemiology of Recurrent Herpes Labialis: A Prevalence Meta-analysis - Alberto Rodriguez-Archilla; Maria Rosa Guerrero-Campos (Current Medical Issues)
Recurrent herpes labialis (RHL) is a highly prevalent lesion and is one of the most common human viral infections worldwide. The aim of this study was to determine the pooled prevalence of RHL worldwide and in different continents, distinguishing between child and adult populations. A search for studies on RHL epidemiology was performed in the following databases: PubMed (MEDLINE, Cochrane Library), Web of Science, and Scopus. The estimation of the pooled proportion was carried out with the generic inverse variance method, using the standard error of the proportion with 95% confidence intervals. Twenty-eight studies with 143,513 participants were included in this meta-analysis. The pooled prevalence of RHL worldwide was 14%, with 3% observed in the pediatric population and 17% in the adult population. By continent, the pooled prevalence of RHL was, in decreasing order, 21% in North America (nine studies), 15% in Africa (two studies), 14% in South America (five studies), 13% in Europe (twelve studies), and 7% in Asia (four studies). RHL is a very common condition, affecting approximately 1 in 7 people. RHL manifests at a significantly higher frequency in the adult population than in the pediatric population.